ETIKA DAN RISIKO KECERDASAN ARTIFISIAL GENERATIF: IMPLIKASI DALAM PENDIDIKAN AGAMA ISLAM DAN MASYARAKAT DIGITAL - Shokhibul Mighfar; Moh. Hafid; Iklilah Qotrinnada (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
Generative Artificial Intelligence (AI) has increasingly influenced educational practices, including Islamic Religious Education (IRE), by enabling automated content creation, AI-based assessment, and adaptive learning. However, its use also raises ethical concerns related to transparency, fairness, copyright, religious misinformation, data bias, and student privacy. This article critically examines the concepts, implementation, ethical dimensions, and potential risks of generative AI in education, with particular attention to its relevance within IRE. Employing a systematic literature review of indexed academic publications, international policy reports, and ethical frameworks for AI in education, the study finds that generative AI can serve as an effective supportive technology for IRE when used responsibly and grounded in core Islamic values, including trustworthiness (amanah), justice (‘adl), honesty (ṣidq), and public interest (maṣlaḥah). The findings reaffirm the central role of IRE teachers as moral guides, interpreters of Islamic teachings, and pedagogical decision-makers, while positioning generative AI as an assistive tool that enhances learning rather than replacing the educator’s moral and spiritual authority. This study contributes both theoretically and practically to the development of ethical, inclusive, and context-sensitive policies and practices for the use of generative AI in Islamic Religious Education.